H-inf robust controller for autonomous helicopter hovering control - Tijani, Ismaila; Akmeliawati, Rini; Legowo , Ari; Budiyono, Agus; Abdul Muthalif, Asan Gani (Emerald, 2011)
Among the major challenges associated with the deployment of autonomous small scale helicopters in civilian UAV applications is the requirement for reliable control scheme. This is due not only to the inherent complexity of the helicopter dynamics, but to the vulnerability of the system to various uncertainties as a result of difficulty in obtaining high fidelity dynamic model, nonlinearities, and external disturbances (e.g. wind gust). This has necessitated the recent research effort in developing reliable control scheme for autonomous helicopter applications. This work presents the development of robust controller for smooth hovering operation required for many autonomous-helicopter operations using H¥ loop shaping technique incorporating the Vinnicombe-gap (v-gap) metric for validation of robustness to uncertainties due to parameter variation in the system model. Simulation study was conducted to evaluate the performance of the designed controller for robust stability to uncertainty, disturbance rejection, and time-domain response in line with ADS-33E level1 requirements. The results obtained show the effectiveness of the designed controller.